The Effect of Kang Duding Exercise on The Quality of Life in Menopausal Women - Fitri, Mustika; Mukarrahmah, Laillah; Fitriana, Lisna Anisa; Sulastri, Afianti; Zaky, Muhammad; Williyanto, Septian; Darmawati, Irma; Zainal Abidin, Nor Eeza (Universitas Pendidikan Indonesia, 2023)
Menopause is recognized for inducing various complaints in women, including common experiences such as dizziness, fatigue, and anxiety. Physical exercise has been scientifically proven to enhance both physical and psychological performance. Regular exercise contributes to improved cardiovascular health, increased strength and endurance, reduced stress and anxiety, enhanced cognitive function, and overall well-being and quality of life. Quality of life encompasses an individual's satisfaction with various aspects of life, including the physical, psychological, social, and environmental dimensions. This study seeks to investigate the impact of exercise on the quality of life among menopausal women, employing an experimental design with a control group and a 12-week pre and post-test. The study involved 32 women aged 45-55 years, divided into two groups: one engaging in Kang Duding exercises (2 sessions of 60 minutes per week) and a control group without intervention. The assessment of quality of life utilized the WHO-QoL questionnaire. The results revealed a significant improvement in all domains of quality of life (QoL) among menopausal women engaging in Kang Duding exercise on physical (p=0.009), psychological (p=0.006), social (p=0.008), and environmental (p=0.029). Physical activity emerges as a key factor contributing to enhanced quality of life, operating through various mechanisms. In conclusion, this study establishes that Kang Duding exercise effectively enhances the quality of life in menopausal women. The findings underscore the significance of incorporating structured physical activity interventions to promote the overall well-being of women during the menopausal transition.